Faza preizkusa sklepčnosti tožbe - Rozman, Til (Pravnik, 2014)
In the article the author addresses and briefly describes current legal regulation of the institute of conclusiveness of an action and differs it from the preliminary examination of an action; conclusiveness is not a prerequisite for the completeness of an action. It is found that current legal regulation is suboptimal, especially in one aspect - although the claim is not founded upon the facts stated in the action, the action (which contains all matter set forth in Article 180 of the Civil Procedure Act and in respect of which the due amount of court fee has been paid) shall be served by the court upon the defendant to make a defence plea and the defendant shall be instructed by the court that in the event of his failure to file a defence plea within the determined time limit, or if his defence plea does not contain a statement of grounds, the court will render a default judgment. This question is analysed with regard to the valid and comparative regulatory framework and legal theory. The author concludes with the proposal to amend the Civil Procedure Act.
Keywords: pravdni postopek; tožbe